PELAYANAN KESEHATAN PADA LANSIA DENGAN HIPERTENSI DI TINGKAT PELAYANAN PRIMER: SYSTEMATIC REVIEW - Kurniawan, Didi; Rekawati, Etty; Sahar, Junaiti (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022, 2022)
Patients with hypertension continue to increase in line with the increase in life expectancy. Hypertension is very dangerous because it can cause heart attack, stroke, kidney failure and even death. Therefore, health services for the elderly with hypertension need serious attention from primary health care providers. Based on these facts, a systematic review was carried out with the aim of providing an overview of the implementation of health services for the elderly with hypertension at the primary service level. The method used is a systematic literature review (systematic review) of various research results sourced from electronic data. Literature searches were conducted online using the ScienceDirect, Scopus, Pubmed, ProQuest, Clinicalkey, and Google Scholar databases. The keywords used in the search for reference sources are “management hypertension”, “elderly”, and “primary care” and are limited to 2016 to 2021. The results of this systematic review reveal that health services at the primary care level have used various approaches such as increasing family involvement, using SMS, telemonitoring, cellular phone-based self-management, and direct family visits in the form of the PIS-PK Perkesmas program. The approach method aims to improve the compliance of elderly patients with hypertension in carrying out pharmacological and non-pharmacological therapy. The conclusion is that primary care must continue to be developed in line with advances in information technology without compromising direct service to patients and improving the quality of primary health care providers.